Voodoo Liability: Joint Enterprise Prosecution as an Aspect of Intensified Criminalisation - Peter A Squires (Oñati Socio-Legal Series)
Following the collapse of a number of 'gang-related' prosecutions in England and Wales from the late 1990s, the police and Crown Prosecution Service revived a practice of 'joint enterprise' prosecution. Joint enterprise was a historic common law principle holding co-defendants equally responsible for offences which appeared to evince a common collective purpose. Unfortunately, over time, a combination of (apparently 'wayward') judicial interpretation, and police and prosecutorial practice contributed to a lowering of the threshold of 'joint liability' such that involvement in a gang, and 'bad character' evidence admitted at trial were taken to imply the 'foreseeability' of violent offences. The apparent tendency of the police to over-define criminal activity by young black males as 'gang-related' has led to the construction of a spurious and 'voodoo criminal liability' leading to the intensified criminalisation (over-prosecution and over-incarceration) of young black men. Between the first presentations of the paper and the written version which follows, the law was amended (R v Jogee 2016) but, as will be argued, not in a way which fundamentally changes the construction of 'joint liability' discussed here.